Chemical and Clinical Analysis of Blood Plasma Components and their Role in the Early Detection of Pathological Disorders - Mageed, Fatimah Abdul Razzak; Hadi, Mohammed Adel; Jumaa, Zainab Kamal Kadem; Koba, Afnan Sabah Mohammed (American Journal of Biomedicine and Pharmacy, 2025)
Blood plasma is an important diagnostic medium for a variety of pathological disorders, and it has the potential for enabling early-stage disease detection due to its distinct component profile. The present work aims to analyze and summarize the various chemical and clinical components present within blood plasma toward the goal of early-stage disease detection. Existing works have reported on the substantial plasma component profile but suffer from a mostly qualitative discussion of candidate markers. There is still an opportunity to deliver a more quantitative review specifically focused on the analysis of plasma components and on those relevant to early-stage detection of diseases as diverse as cardiovascular and renal disorders, diabetes, and infection. Early detection of pathological disorders is a prime objective of clinical analyses. Blood is the most widely studied biofluid in clinical diagnostics due to its ease of access and rich information. Blood plasma is of particular interest because it is the liquid portion of blood following complete coagulation and contains a chemical composition reflecting a larger area of the body than other sample types such as serum or whole blood. Because disease typically influences the chemistry of the body, changes in blood plasma composition have the potential to serve as diagnostic biomarkers for clinical pathologies.